On the solution of the nonlinear Korteweg-de Vries equation by the homotopy perturbation method - Yildirim, Ahmet (Communications in numerical methods in engineering, 2009)
In this paper, the homotopy perturbation method is used to implement the nonlinear Korteweg–de Vries equation. The analytical solution of the equation is calculated in the form of a convergent power series with easily computable components. A suitable choice of an initial solution can lead to the needed exact solution by a few iterations. Copyright © 2008 John Wiley & Sons, Ltd.